The Battle of Orgreave - Figgis, Mike; Deller, Jeremy; Barkof, David; Eley, Mike; Fenton, Nick (Artangel Media, 2006)
A vivid reconstruction of, and documentary about, a key battle between miners and police in the 1984/85 miners strike. Director Mike Figgis and Turner Prize-winning artist Jeremy Deller collaborated to investigate a key moment in Northern English social history and rekindle memories for those whose lives were changed by the industrial dispute. [www.channel4.com]